Evaluation of Arterial Spin Labeling MRI—Comparison with (15)O-Water PET on an Integrated PET/MR Scanner - Fahlström, Markus (Diagnostics (Basel), 2021)
Cerebral blood flow (CBF) measurements are of high clinical value and can be acquired non-invasively with no radiation exposure using pseudo-continuous arterial spin labeling (ASL). The aim of this study was to evaluate accordance in resting state CBF between ASL (CBF(ASL)) and (15)O-water positron emission tomography (PET) (CBF(PET)) acquired simultaneously on an integrated 3T PET/MR system. The data comprised ASL and dynamic (15)O-water PET data with arterial blood sampling of eighteen subjects (eight patients with focal epilepsy and ten healthy controls, age 21 to 61 years). (15)O-water PET parametric CBF images were generated using a basis function implementation of the single tissue compartment model. Cortical and subcortical regions were automatically segmented using Freesurfer. Average CBF(ASL) and CBF(PET) in grey matter were 60 ± 20 and 75 ± 22 mL/100 g/min respectively, with a relatively high correlation (r = 0.78, p < 0.001). Bland-Altman analysis revealed poor agreement (bias = −15 mL/100 g/min, lower and upper limits of agreements = −16 and 45 mL/100 g/min, respectively) with a negative relationship. Accounting for the negative relationship, the width of the limits of agreement could be narrowed from 61 mL/100 g/min to 35 mL/100 g/min using regression-based limits of agreements. Although a high correlation between CBF(ASL) and CBF(PET) was found, the agreement in absolute CBF values was not sufficient for ASL to be used interchangeably with (15)O-water PET.